Risk factors for neonatal mortality at Moewardi Hospital, Surakarta - Dwi Hidayah; Yulidar Hafidh (Indonesian Pediatric Society, 2014)
Background Neonatal mortality remains a major concern indeveloping countries. Identifying potential risk factors is importantin order to decrease the neonatal mortality rate. In MoewardiHospital, Surakarta, the risk factors for neonatal mortality havenot been assessed.Objective To evaluate potential risk factors of n eonatalmortality.Methods We reviewed medical records of all neonates hospitalizedin the neonatal intensive care unit (NICU) at Dr. MoewardiHospital from January to December 2011. Analyzed variables weresex, birth weight, gestational age, maternal age, place of delivery,mode of delivery, and sepsis. Data were analyzed by Chi square andbinary logistic regression with 95% confidence intervals (CI).Results Out of841 neonates, the mortality rate was 212 (25.2%).Univariate logistic regression revealed that the significant riskfactors for neonatal mortality were preterm (OR 4.41 ; 95%CI4.24 to 4.57; P=0.0001) , low bir th weight (OR 4.30; 95%CI4.13 to 4.47; P=0.0001), sepsis (OR 2.99; 95%CI 2.81 to 3.17;P=0.0001), maternal age 2:35 years (OR 1.53; 95%CI 1.37 to1.70), and non-spontaneous delivery (OR 1.67; 95%CI 1.50 to1.84). Further multivariate regression analysis revealed that thesignificant risk factors were preterm (OR 2.2 7; 95%CI 2.05 to 2.48;P=0.0001), low birth weight (OR 2.49; 95%CI 2.27 to 2.71; P=0.0001), and sepsis (OR 2.50; 95%CI 2.30 to 2.69; P= 0.0001).Conclusion The risk factors for neonatal mortality in the NICUare preterm, low birth weight, and sepsis.